Carbon-coated solid electrolyte, battery and electrical equipment

By forming a characteristic carbon cladding layer on the solid electrolyte, the side reactions and low conductivity problems of solid electrolyte in lithium-ion batteries are solved, and the performance of the battery is significantly improved.

CN118825456BActive Publication Date: 2025-03-25SONGSHAN LAKE MATERIALS LAB +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411298726.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-03-25
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The application of solid electrolytes in lithium-ion batteries is limited by the side reactions of electrode materials and the low ionic conductivity, which affects its safety performance and overall performance.

Method used

The solid electrolyte is adopted to coat the electrolyte core, which includes the electrolyte core and the carbon cladding layer coated on the surface of the electrolyte core. The X-ray photoelectron spectroscopy test results of the carbon cladding have a specific sp3 and sp2 hybrid peak ratio, ensuring that the structure of the carbon cladding layer is strong and has good ion conduction properties.

Benefits of technology

It effectively suppresses the side reaction between the electrolyte core and the electrode material, and significantly improves the ionic conductivity of the solid electrolyte, thereby improving the charge and discharge specific capacity and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118825456B_ABST
    Figure CN118825456B_ABST
Patent Text Reader

Abstract

The present disclosure provides a carbon-coated solid electrolyte, a battery, and an electrical device. The carbon-coated solid electrolyte includes an electrolyte core and a carbon coating layer coated on the surface of the electrolyte core, and the X-ray photoelectron spectroscopy test results of the carbon coating layer have the following characteristics: the carbon element has a first peak corresponding to sp3 hybridization and a second peak corresponding to sp2 hybridization, and the ratio of the intensity of the first peak to the intensity of the second peak is ≥0.1. The use of a carbon coating layer with a ratio of the intensity of the first peak to the intensity of the second peak ≥0.1 can effectively avoid the deterioration caused by the contact between the electrolyte core and the electrode active material, and can also improve the ionic conductivity of the solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a carbon-coated solid electrolyte, a battery and an electrical device. Background Art

[0002] A battery is a device that can store and release electrical energy. Lithium-ion batteries are the most widely used battery system in commercial applications. Traditional lithium-ion batteries usually require the use of liquid electrolytes. Although they can provide higher ionic conductivity, they also cause problems such as electrode side reactions and poor thermal stability, resulting in poor battery safety performance. The introduction of solid-state electrolytes can not only improve the safety performance of batteries, but also optimize the overall performance of batteries, and has high application potential.

[0003] However, solid electrolytes currently still have the problems of easy side reactions with electrode materials and low ionic conductivity, which limits the further application of solid electrolytes. Summary of the invention

[0004] Based on this, it is necessary to provide a carbon-coated solid electrolyte to address the problems in the above-mentioned background technology, which can effectively improve the ion conductivity while suppressing the side reactions with the electrode materials.

[0005] According to some embodiments of the present disclosure, a carbon-coated solid electrolyte is provided, which includes an electrolyte core and a carbon coating layer coated on the surface of the electrolyte core, and the carbon coating layer has the following characteristics in the X-ray photoelectron spectroscopy test results: the carbon element has a first peak position corresponding to sp3 hybridization and a second peak position corresponding to sp2 hybridization, and the ratio of the intensity of the first peak position to the intensity of the second peak position is ≥0.1.

[0006] In some embodiments of the present disclosure, in the X-ray photoelectron spectroscopy test results of the carbon coating layer, the carbon element has a composite peak between 284eV and 287eV formed by the superposition of the first peak position and the second peak position, and the composite peak is subjected to peak separation processing to form a first peak position between 284 and 285eV and a second peak position between 285 and 286eV, respectively.

[0007] In some embodiments of the present disclosure, the carbon coating layer further includes oxygen element, and the X-ray photoelectron spectroscopy test results of the carbon coating layer also have the following characteristics: the oxygen element has peak positions between 530eV~532eV and 528eV~530eV.

[0008] In some embodiments of the present disclosure, the thickness of the carbon coating layer is 1 nm to 100 nm.

[0009] In some embodiments of the present disclosure, the material of the electrolyte core includes one or more of an oxide solid electrolyte, a halide solid electrolyte, and a polymer solid electrolyte;

[0010] The oxide solid electrolyte is selected from one or more of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium lanthanum zirconium oxide and lithium phosphorus oxygen nitrogen;

[0011] The halide solid electrolyte is selected from one or more of lithium indium chloride, lithium yttrium chloride and lithium zirconium chloride.

[0012] In some embodiments of the present disclosure, the particle size of the electrolyte core is 100 nm to 100 μm.

[0013] The present disclosure also provides a method for preparing the above-mentioned solid electrolyte, which comprises the steps of preparing and forming a carbon coating layer on the surface of the electrolyte core;

[0014] The steps of preparing and forming the carbon coating layer include: mixing a carbon source precursor with an electrolyte core, and calcining the mixture by microwave heating in a protective gas to form a carbon coating layer on the surface of the electrolyte core; or,

[0015] The steps of preparing and forming a carbon coating layer include: placing an electrolyte core in a deposition chamber, introducing a carbon source gas into the deposition chamber, and depositing a carbon coating layer on the surface of the electrolyte core by direct photochemical vapor deposition or plasma enhanced chemical vapor deposition.

[0016] The present disclosure also provides a battery, which includes the carbon-coated solid electrolyte according to any of the above embodiments.

[0017] In some embodiments of the present disclosure, the positive electrode of the battery includes a positive electrode active layer, and the carbon-coated solid electrolyte is disposed in the positive electrode active layer; or,

[0018] The positive electrode of the battery comprises a positive electrode active layer and an ion-conducting layer which are stacked, and the carbon-coated solid electrolyte is arranged in the ion-conducting layer; or,

[0019] The battery comprises a positive electrode, a negative electrode and a separator arranged between the positive electrode and the negative electrode, and the carbon-coated solid electrolyte is arranged on a side of the separator close to the positive electrode.

[0020] In some embodiments of the present disclosure, the battery is a lithium-ion battery, a solid-state battery, or a semi-solid-state battery.

[0021] The present disclosure also provides an electrical device, which includes a functional body and a battery as described in any of the above embodiments, wherein the battery is used to supply energy to the functional body.

[0022] The carbon coating contains not only carbon atoms bonded in sp2 hybridization, but also carbon atoms bonded in sp3 hybridization. Compared with sp2 hybridized carbon atoms, the structure formed by carbon atoms bonded in sp3 hybridization is more solid, and the effect of carbon atoms bonded in sp3 hybridization on promoting ion conduction is more obvious. The use of a carbon coating with a ratio of the intensity of the first peak to the intensity of the second peak ≥ 0.1 can effectively avoid the deterioration caused by the contact between the electrolyte core and the electrode active material, and can also improve the ionic conductivity of the solid electrolyte.

[0023] Experimental verification has shown that using the carbon-coated solid electrolyte to modify the positive electrode part of the battery can effectively improve the battery's charge and discharge capacity and cycle stability.

[0024] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present disclosure. For ordinary technicians in this field, drawings of other embodiments can be obtained based on these drawings without creative work.

[0026] Figure 1 A schematic diagram of the steps of a method for preparing a carbon-coated solid electrolyte;

[0027] Figure 2 Schematic diagram of the morphology of the carbon-coated solid electrolyte in Example 1 observed using a transmission electron microscope;

[0028] Figure 3 The X-ray photoelectron spectroscopy test result diagram of the carbon-coated solid electrolyte of Example 1 and the corresponding processed curve, wherein the left figure is the test result diagram, and the right figure is the curve after fitting and peak separation of the left figure;

[0029] Figure 4 The graphs are the X-ray photoelectron spectroscopy test results of the carbon-coated solid electrolyte of Comparative Example 1 and the corresponding processed curves, wherein the left graph is the test result graph, and the right graph is the curve after fitting processing of the left graph. DETAILED DESCRIPTION

[0030] To facilitate understanding of the present invention, a more comprehensive description of the present invention is provided below. The preferred embodiments of the present invention are given herein. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the content of the present invention more thorough and comprehensive.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this document pertains. The terms used herein in the specification of this document are only for describing specific embodiments and are not intended to limit this document.

[0032] It should be understood that when an element or layer is referred to as being "on, "adjacent to, "connected to, or "coupled to" another element or layer, it may be directly on, adjacent to, connected to, or coupled to the other element or layer, or there may be intervening elements or layers. In contrast, when an element is referred to as being "directly on, "directly adjacent to, "directly connected to, or "directly coupled to" another element or layer, there may be no intervening elements or layers. It should be understood that although the terms first, second, third, etc. may be used to describe various elements, components, regions, layers, and / or portions, these elements, components, regions, layers, and / or portions should not be limited by these terms. These terms are merely used to distinguish one element, component, region, layer, or portion from another element, component, region, layer, or portion.

[0033] Spatially relative terms such as "under," "beneath," "below," "under," "above," "above," and the like may be used herein for ease of description to describe the relationship of one element or feature to other elements or features. It should be understood that the spatially relative terms are intended to also include different orientations of the device in use and operation. For example, if the device in the accompanying drawings is flipped, then the elements or features described as "under other elements" or "under" or "under" will be oriented as "over" the other elements or features. Thus, the exemplary terms "under" and "under" may include both upper and lower orientations. The device may be otherwise oriented (e.g., rotated 90 degrees or other orientations) and the spatial descriptors used may be interpreted accordingly.

[0034] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be a limitation of the present disclosure. When used herein, the singular forms "a", "an" and "the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.

[0035] In conventional technology, the material of the carbon coating layer used to coat the solid electrolyte is usually an amorphous carbon material and / or a graphitized carbon material, wherein the carbon atoms in the graphitized carbon material form bonds in a sp2 hybridized manner, and the cap material shows a peak corresponding to the sp2 hybridization in the X-ray photoelectron spectroscopy test results. The graphitized carbon material has a high electrical conductivity, which is conducive to promoting the conduction of electrons.

[0036] In the first aspect, the present disclosure provides a carbon-coated solid electrolyte, which includes an electrolyte core and a carbon coating layer coated on the surface of the electrolyte core, and the X-ray photoelectron spectroscopy test results of the carbon coating layer have the following characteristics: the carbon element has a first peak position corresponding to sp3 hybridization and a second peak position corresponding to sp2 hybridization, and the ratio of the intensity of the first peak position to the intensity of the second peak position is ≥0.1.

[0037] The carbon coating contains not only carbon atoms bonded in sp2 hybridization, but also carbon atoms bonded in sp3 hybridization. Compared with sp2 hybridized carbon atoms, the structure formed by carbon atoms bonded in sp3 hybridization is more solid, and the effect of carbon atoms bonded in sp3 hybridization on promoting ion conduction is more obvious. The use of a carbon coating with a ratio of the intensity of the first peak to the intensity of the second peak ≥ 0.1 can effectively avoid the deterioration caused by the contact between the electrolyte core and the electrode active material, and can also improve the ionic conductivity of the solid electrolyte.

[0038] Experimental verification has shown that using the carbon-coated solid electrolyte to modify the positive electrode part of the battery can effectively improve the battery's charge and discharge capacity and cycle stability.

[0039] It can be understood that in the X-ray photoelectron spectroscopy test results, the actual positions of the first peak corresponding to sp3 hybridization and the second peak corresponding to sp2 hybridization are related to the overall structure and composition of the material, which makes the actual positions of the first peak and the second peak different in different carbon coating layers. In addition, the first peak and the second peak may also form a composite peak due to partial overlap, but technicians can analyze the hybridization state corresponding to each peak from the X-ray photoelectron spectroscopy test results in combination with common knowledge in the field and technical means such as peak separation processing.

[0040] As an example of this embodiment, the ratio of the intensity of the first peak to the intensity of the second peak can be 0.1, 0.3, 0.5, 1, 2, 3, 5, 7, 10, 20, 30, 50, 100, or the ratio of the intensity of the first peak to the intensity of the second peak can be between any two of the above ratios.

[0041] It can be understood that the ratio of the intensity of the first peak to the intensity of the second peak herein may have no upper limit. For example, when the second peak is substantially absent in the carbon coating layer, the intensity ratio may be infinite.

[0042] As an example of this embodiment, in the X-ray photoelectron spectroscopy test results of the carbon coating layer, the carbon element has a composite peak between 284eV and 287eV formed by the superposition of the first peak position and the second peak position. After peak separation processing, the composite peak forms a first peak position between 284 and 285eV and a second peak position between 285 and 286eV.

[0043] As an example of this embodiment, the carbon coating layer also includes oxygen. Further, the X-ray photoelectron spectroscopy test results of the carbon coating layer also have the following characteristics: the oxygen element has peaks between 530eV~532eV and 528eV~530eV. The present disclosure has found in the research process that when the carbon coating layer is present and the oxygen element has peaks between 530eV~532eV and 528eV~530eV, the carbon-coated solid electrolyte has better ion conductivity.

[0044] As an example of this embodiment, the thickness of the carbon coating layer is 1 nm to 100 nm. The carbon coating layer within this thickness range can take into account both good protection and the role of promoting ion conduction. When the thickness is too thick, the excessively thick carbon coating layer may block the normal transmission of ions.

[0045] As an example of this embodiment, the thickness of the carbon coating layer is 1 nm to 20 nm. For example, the thickness of the carbon coating layer can be 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 7 nm, 10 nm, 12 nm, 15 nm, 17 nm, 20 nm, or the thickness of the carbon coating layer can be between any two of the above thicknesses.

[0046] As an example of this embodiment, the material of the electrolyte core includes one or more of an oxide solid electrolyte, a halide solid electrolyte, and a polymer solid electrolyte.

[0047] In this example, the oxide solid electrolyte is selected from lithium aluminum titanium phosphate (Li 1.5 Al 0.5 Ti 1.5 (PO4))、Lithium Aluminum Germanium Phosphate(Li 1.5 Al 0.5 Ge 1.5 (PO4)), lithium lanthanum zirconium oxide (Li7La3Zr2O 12 ) and one or more of lithium phosphorus oxynitride (LiPON).

[0048] In this example, the halide solid electrolyte is selected from one or more of lithium indium chloride (Li3InCl6), lithium yttrium chloride (Li3YCl6) and lithium zirconium chloride (Li2ZrCl6).

[0049] As an example of this embodiment, the particle size of the electrolyte core is 100nm~100μm. For example, the particle size of the electrolyte core can be 100nm, 500nm, 1μm, 5μm, 10μm, 15μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, or the particle size of the electrolyte core can also be between any two of the above particle sizes.

[0050] In a second aspect, the present disclosure also provides a method for preparing a carbon-coated solid electrolyte, which includes the step of forming a carbon coating layer on the surface of an electrolyte core.

[0051] Figure 1 Schematic diagram of the steps of preparing a carbon-coated solid electrolyte. Figure 1 As shown, the method for preparing the carbon-coated solid electrolyte includes the following steps S1 to S2.

[0052] Step S1, providing an electrolyte core.

[0053] As some examples of this embodiment, the material of the electrolyte core includes one or more of an oxide solid electrolyte, a halide solid electrolyte, and a polymer solid electrolyte.

[0054] In this example, the oxide solid electrolyte is selected from lithium aluminum titanium phosphate (Li 1.5 Al 0.5 Ti 1.5 (PO4))、Lithium Aluminum Germanium Phosphate(Li 1.5 Al 0.5 Ge 1.5 (PO4)), lithium lanthanum zirconium oxide (Li7La3Zr2O 12 ) and one or more of lithium phosphorus oxynitride (LiPON).

[0055] In this example, the halide solid electrolyte is selected from one or more of lithium indium chloride (Li3InCl6), lithium yttrium chloride (Li3YCl6) and lithium zirconium chloride (Li2ZrCl6).

[0056] Step S2, forming a carbon coating layer on the surface of the electrolyte core.

[0057] As an example of this embodiment, the step of preparing and forming a carbon coating layer includes: mixing a carbon source precursor with an electrolyte core, heating the mixture in a protective gas by microwaves for calcination, and forming a carbon coating layer on the surface of the electrolyte core. Compared with the conventional heat conduction heating method, calcination by directly heating the carbon source precursor with microwaves can transform the carbon source precursor into an sp3 hybridized carbon element, so that the carbon element in the carbon coating layer has an sp3 hybridized component.

[0058] As an example of this embodiment, the protective gas should be selected from gases that do not react with the carbon source precursor and the electrolyte core. In some examples, the protective gas is selected from one or more of argon and nitrogen.

[0059] As an example of this embodiment, in the process of calcining by microwave heating, the mixed material can be controlled to be heated by microwave to 180°C~1500°C. It can be understood that for different carbon source precursors, the heating temperature may be different, and the specific structure of the carbon coating layer to be generated should be regulated. The heating temperature can be controlled by controlling the power of the microwave.

[0060] As an optional example of this embodiment, the mixed material can be controlled to be heated by microwaves to 500° C. to 700° C. As some examples, the mixed material can be controlled to be heated by microwaves to 500° C., 520° C., 550° C., 570° C., 600° C., 620° C., 650° C., 670° C., 700° C., or the mixed material can be controlled to be heated by microwaves to any temperature between the above two temperatures.

[0061] As an example of this embodiment, the mixed material can be controlled to be heated by microwaves for 2 hours to 8 hours. For example, the time for the mixed material to be heated by microwaves can be controlled to be 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, or 8 hours, or the time for the mixed material to be heated by microwaves can be controlled to be between any two of the above times.

[0062] It can be understood that by controlling the temperature and heating time of microwave heating, the intensity ratio of the first peak and the second peak in the formed carbon coating layer can be correspondingly controlled.

[0063] As an example of this embodiment, the mass ratio of the carbon source precursor to the electrolyte core may be (1:10) to (10:1).

[0064] As an example of this embodiment, the carbon source precursor includes one or more of phenolic resin, furfural resin, epoxy resin, urea-formaldehyde resin, asphalt, citric acid, glucose, sucrose, polyvinyl chloride, and polyvinyl butyral.

[0065] As another example of this embodiment, the step of preparing and forming a carbon coating layer includes: placing an electrolyte core in a deposition chamber, introducing a carbon source gas into the deposition chamber, and depositing a carbon coating layer on the surface of the electrolyte core by direct photochemical vapor deposition or plasma enhanced chemical vapor deposition. Compared with the conventional thermal decomposition deposition method, the direct photochemical vapor deposition or plasma enhanced chemical vapor deposition deposition method can make the carbon atoms generated by decomposition bonded by sp3 hybridization, so that the carbon element in the carbon coating layer has an sp3 hybridized component.

[0066] It can be understood that by controlling the light intensity during the photochemical vapor deposition process and the RF power during the plasma enhanced chemical vapor deposition process, the intensity ratio of the first peak and the second peak in the formed carbon coating layer can be correspondingly controlled.

[0067] As an example of this embodiment, a protective gas is also introduced into the deposition chamber. The protective gas should be selected from gases that do not react with the carbon source precursor and the electrolyte core. In some examples, the protective gas is selected from one or more of argon and nitrogen.

[0068] As an example of this embodiment, during the deposition process, the ambient temperature in the deposition chamber may be controlled to be 180° C. to 1500° C.

[0069] As an optional example of this embodiment, the ambient temperature in the deposition chamber may be controlled to be 500° C. to 700° C. As some examples, the ambient temperature in the deposition chamber may be controlled to be 500° C., 520° C., 550° C., 570° C., 600° C., 620° C., 650° C., 670° C., 700° C., or the ambient temperature in the deposition chamber may be controlled to be between any two of the above temperatures.

[0070] As an example of this embodiment, the deposition time can be controlled to be 1 hour to 10 hours. For example, the deposition time can be controlled to be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 10 hours, or the deposition time can be controlled to be between any two of the above times.

[0071] As an example of this embodiment, the carbon source gas includes one or more of acetylene, ethylene, methane, ethane, propane, and n-butane.

[0072] As an example of this embodiment, the flow rate of the carbon source gas introduced into the deposition chamber may be 0.1 L / min to 10 L / min.

[0073] In a third aspect, the present disclosure further provides a battery. The battery includes the solid electrolyte in the above embodiment. It is understood that the battery should include a positive electrode and a negative electrode. The solid electrolyte can be arranged inside the positive electrode, inside the negative electrode, or between the positive electrode and the negative electrode of the battery.

[0074] As an example of this embodiment, the positive electrode of the battery includes a positive electrode active layer, and the carbon-coated solid electrolyte is disposed in the positive electrode active layer.

[0075] As another example of this embodiment, the positive electrode of the battery includes a positive electrode active layer and an ion-conducting layer that are stacked, and the carbon-coated solid electrolyte is disposed in the ion-conducting layer.

[0076] As another example of this embodiment, the battery includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, and the carbon-coated solid electrolyte is disposed on a side of the separator close to the positive electrode.

[0077] It can be understood that the carbon-coated solid electrolyte includes a carbon coating layer, and the structure of the carbon coating layer is relatively strong and stable, which is conducive to avoiding direct contact between the solid electrolyte and the positive electrode active material in the positive electrode active layer, thereby ensuring the material stability of the electrolyte core. At the same time, the carbon-coated solid electrolyte can also improve the ion conductivity of the positive electrode active layer.

[0078] As an example of this embodiment, the positive electrode may include a positive electrode sheet. The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer.

[0079] In some examples, the positive electrode active layer includes a positive electrode active material selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, layered ternary positive electrode materials, spinel lithium nickel manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese phosphate, and lithium cobalt phosphate.

[0080] In some examples, the positive electrode active layer may further include one or more of a conductive agent and a binder.

[0081] In the positive electrode active layer, the conductive agent may be selected from one or more of conductive carbon black, carbon nanotubes, graphene and carbon nanofibers.

[0082] In the positive electrode active layer, the binder may be selected from one or more of polyvinyl pyrrolidone, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, carboxymethyl cellulose and a copolymer of styrene and butadiene.

[0083] As an example of this embodiment, the negative electrode may include a negative electrode sheet. The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material.

[0084] In some examples, the negative electrode active material includes one or more of graphite, silicon, silicon carbon, metallic lithium and lithium titanate. In addition, silicon-based materials may also be included. The silicon-based material may include one or more of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. In some specific examples, the silicon-based material uses silicon-oxygen materials or pre-lithiated silicon-oxygen particles.

[0085] In some examples, the negative electrode active layer may further include one or more of a conductive agent and a binder.

[0086] In the negative electrode active layer, the conductive agent may be selected from one or more of conductive carbon black, carbon nanotubes, graphene and carbon nanofibers.

[0087] In the negative electrode active layer, the binder may be selected from one or more of polyvinyl pyrrolidone, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, carboxymethyl cellulose and a copolymer of styrene and butadiene.

[0088] In a fourth aspect, the present disclosure further provides an electrical device, which includes a functional body and a battery as in any of the above embodiments, wherein the battery is used to supply energy to the functional body.

[0089] As an example of this embodiment, the power-consuming device may be a mobile phone, a laptop computer, a smart watch, or an electric car.

[0090] In order to facilitate understanding of the specific implementation methods and beneficial effects of the present disclosure, the present disclosure also provides the following more specific examples and comparative examples. Through the description of the examples and comparative examples, the beneficial effects of the present disclosure will also be more obvious.

[0091] Example 1

[0092] Preparation of carbon-coated solid electrolyte: Use lithium aluminum titanium phosphate with a particle size of 1 μm as the electrolyte core, stir and mix it with sucrose at a mass ratio of 10:1 to form a mixed material. Transfer the mixed material to a microwave sintering chamber, keep the microwave sintering chamber in an argon atmosphere, use microwaves to heat the mixed material to 650°C and calcine for 2 hours, then cool to room temperature to form a carbon-coated solid electrolyte material.

[0093] Preparation of positive electrode sheet: The carbon-coated solid electrolyte, ternary positive electrode, polyvinylidene fluoride and SuperP are uniformly mixed in a mass ratio of 5:90:3:2 and dispersed in nitrogen-methylpyrrolidone to form a slurry. The slurry is coated on the surface of aluminum foil and then dried to form a positive electrode sheet.

[0094] Preparation of electrolyte: A mixed solvent of EC, DMC and FEC was used, wherein the volume ratio of EC, DMC and FEC was 4.8:4.8:0.4, and lithium hexafluorophosphate was dissolved in the mixed solvent, and the molar concentration of lithium hexafluorophosphate was 1 mol / L.

[0095] Preparation of battery: The above-mentioned positive electrode plate and lithium plate are assembled in pairs to form a half-battery, and the positive electrode plate and the lithium plate are separated by a Celgard2300 isolation film.

[0096] Example 2

[0097] The difference between Example 2 and Example 1 is only the preparation process of the carbon-coated solid electrolyte. The preparation process of the carbon-coated solid electrolyte in Example 2 is as follows: the carbon-coated solid electrolyte is placed in a direct photochemical vapor deposition chamber, acetylene with a flow rate of 1 L / min is introduced as a carbon source gas, the temperature of the deposition chamber is controlled to be 700°C, and the deposition time is 4 hours. After completion, it is cooled to room temperature to form a carbon-coated solid electrolyte material.

[0098] Example 3

[0099] The difference between Example 3 and Example 1 is only the preparation process of the carbon-coated solid electrolyte. The preparation process of the carbon-coated solid electrolyte in Example 3 is as follows: the carbon-coated solid electrolyte is placed in a plasma enhanced chemical vapor deposition chamber, acetylene with a flow rate of 1 L / min is introduced as a carbon source gas, the temperature of the deposition chamber is controlled to be 700°C, and the deposition time is 4 hours. After completion, it is cooled to room temperature to form a carbon-coated solid electrolyte material.

[0100] Example 4

[0101] The only difference between Example 4 and Example 1 is that Example 4 uses lithium indium chloride as the electrolyte core.

[0102] Example 5

[0103] The difference between Example 5 and Example 1 is only the preparation process of the positive electrode sheet.

[0104] The preparation process of the positive electrode sheet in Example 5 is as follows: lithium iron phosphate, polyvinylidene fluoride and SuperP are uniformly mixed in a mass ratio of 90:3:2 and dispersed in nitrogen methyl pyrrolidone to form a slurry, the slurry is coated on the surface of aluminum foil and then dried to form a positive electrode active layer. Subsequently, the carbon-coated solid electrolyte is dispersed in nitrogen methyl pyrrolidone to form a slurry, the slurry is coated on the surface of the positive electrode active layer and then dried to form a positive electrode sheet.

[0105] Example 6

[0106] The difference between Example 6 and Example 1 is only the preparation process of the positive electrode sheet and the battery.

[0107] The preparation process of the positive electrode sheet in Example 6 is: lithium iron phosphate, polyvinylidene fluoride and SuperP are uniformly mixed in a mass ratio of 90:3:2 and dispersed in nitrogen methyl pyrrolidone to form a slurry, the slurry is coated on the surface of aluminum foil and then dried to form a positive electrode sheet.

[0108] The preparation process of the positive electrode plate in Example 6 is: dispersing the carbon-coated solid electrolyte in nitrogen-methylpyrrolidone to form a slurry, coating the slurry on the surface of the Celgard2300 isolation membrane close to the positive electrode and drying it, and then using the isolation membrane, the above-mentioned positive electrode plate and the lithium sheet to assemble a half-cell.

[0109] Comparative Example 1

[0110] The only difference between Comparative Example 1 and Example 1 is that: in Comparative Example 1, no carbon-coated solid electrolyte is prepared, and the carbon-coated solid electrolyte in Example 1 is replaced by a solid electrolyte when preparing the positive electrode plate.

[0111] Comparative Example 2

[0112] The difference between Comparative Example 2 and Example 1 is only the preparation process of the carbon-coated solid electrolyte. In the preparation of the carbon-coated solid electrolyte in Comparative Example 2, microwave radiation heating is not used, but heat conduction heating is performed by a resistance furnace.

[0113] Comparative Example 3

[0114] The only difference between Comparative Example 3 and Example 2 is the preparation process of the carbon-coated solid electrolyte. In the preparation of the carbon-coated solid electrolyte in Comparative Example 3, a conventional tube furnace is used for deposition instead of a direct photochemical vapor deposition chamber.

[0115] Experiment 1: The morphology of the carbon-coated solid electrolyte in Example 1 was observed using a transmission electron microscope. The morphology of the carbon-coated solid electrolyte can be seen in Figure 2 .

[0116] Experiment 2: X-ray photoelectron spectroscopy was performed on the carbon-coated solid electrolytes of Example 1 and Comparative Example 1, and the results can be seen in Figure 3~Figure 4 . Figure 3 The graphs are the X-ray photoelectron spectroscopy test results of the carbon-coated solid electrolyte of Example 1 and the corresponding processed curves, wherein the left graph is the test result graph, and the right graph is the curve after fitting and peak separation of the left graph. Figure 4 The graphs are the X-ray photoelectron spectroscopy test results of the carbon-coated solid electrolyte of Comparative Example 1 and the corresponding processed curves, wherein the left graph is the test result graph, and the right graph is the curve after fitting processing of the left graph.

[0117] Reference Figure 2 As shown, according to the observation results of the transmission electron microscope, it can be determined that there is an obvious carbon coating layer on the surface of the product prepared in Example 1, and the thickness of the carbon coating layer is less than 10nm, specifically about 3nm.

[0118] Further, refer to Figure 3 As shown, Figure 3 The horizontal axis represents binding energy, and the vertical axis represents intensity. After the peak separation process, the X-ray photoelectron spectroscopy test results of Example 1 have a first peak between 284eV and 285eV, and the intensity of the first peak is recorded as C1. There is a second peak between 283eV and 284eV, and the intensity of the second peak is recorded as C2. The first peak corresponds to sp3 hybridized carbon elements, and the second peak corresponds to sp2 hybridized carbon elements. Obviously, the ratio of the intensity of the first peak C1 to the intensity of the second peak C2 is about 1.4. This shows that there are more sp3 hybridized carbon elements in the carbon coating layer prepared in the preparation process of Example 1.

[0119] Reference Figure 4 As shown, the X-ray photoelectron spectroscopy test results of Comparative Example 1 show only one peak, corresponding to the sp2 hybridized carbon element. This indicates that the carbon coating layer prepared in the preparation process of Comparative Example 1 only contains sp2 hybridized carbon elements, and basically does not contain sp3 hybridized carbon elements.

[0120] Experiment 3: The batteries of the above embodiments and comparative examples were subjected to charge and discharge cycle tests. The test results can be seen in Table 1.

[0121] Table 1

[0122]

[0123] As shown in Table 1, Comparative Example 1 did not prepare a carbon coating on the electrolyte surface, and directly added the solid electrolyte to the positive electrode plate. After 100 cycles, the cycle capacity retention rate of the battery was only 90.36%. Compared with Example 1, the initial discharge specific capacity of Comparative Example 2 is lower, and the cycle capacity retention rate is also lower. Combined with the differences in its preparation process and XPS test results, it can be seen that the difference in the results is mainly due to the fact that the carbon elements in the carbon coating in Comparative Example 2 are mainly sp2 hybridized. This shows that the ion conductivity and structural stability of the carbon coating formed by carbon atoms bonded in an sp2 hybridized manner are not as good as those of the carbon coating formed by carbon atoms bonded in an sp3 hybridized manner.

[0124] Example 2 and Example 3 respectively adopt photochemical deposition and plasma enhanced chemical vapor deposition to prepare the carbon coating layer, and the XPS test results of the products prepared are similar to those of Example 1. The prepared carbon coating layers contain more carbon elements bonded in the sp3 hybridization mode. Therefore, Example 2 and Example 3 can obtain initial discharge specific capacity and cycle capacity retention rate similar to that of Example 1.

[0125] Example 4 uses lithium indium chloride as the solid electrolyte and can also achieve initial discharge specific capacity and cycle capacity retention rate similar to those of Example 1, indicating that the carbon coating layer disclosed in the present invention can be applied to a variety of different solid electrolytes.

[0126] In Example 5, the carbon-coated solid electrolyte is coated on the surface of the positive electrode active layer, and the initial discharge specific capacity and cycle capacity retention rate similar to those in Example 1 can be achieved, indicating that the carbon-coated solid electrolyte coated on the surface of the positive electrode plate can also play its good ion conductive role.

[0127] In Example 6, the carbon-coated solid electrolyte is coated on the surface of one side of the diaphragm close to the positive electrode, and the initial discharge specific capacity and cycle capacity retention rate can be better than those of Example 1, indicating that coating the carbon-coated solid electrolyte on the diaphragm can play a better ion conductive role and is less likely to have a negative impact on the positive electrode plate.

[0128] Please note that the above embodiments are for illustrative purposes only and are not meant to be limiting of this document.

[0129] It should be understood that, unless otherwise specified herein, there is no strict order restriction for the execution of the steps, and the steps may be executed in other orders. Moreover, at least a portion of the steps in the preparation process may include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but may be executed at different times, and the execution order of these sub-steps or stages is not necessarily sequential, but may be executed in turn or alternately with other steps or at least a portion of the sub-steps or stages of other steps.

[0130] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0131] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

Claims

1. A battery, characterized in that: The invention comprises a carbon-coated solid electrolyte, wherein the carbon-coated solid electrolyte comprises an electrolyte core and a carbon coating layer coated on the surface of the electrolyte core, wherein the carbon coating layer has the following characteristics in an X-ray photoelectron spectrum test result: the carbon element has a first peak corresponding to sp3 hybridization and a second peak corresponding to sp2 hybridization, the ratio of the intensity of the first peak to the intensity of the second peak is ≥1, the carbon element has a composite peak between 284eV and 287eV formed by the superposition of the first peak and the second peak, and the composite peak is subjected to peak separation to form a first peak between 284eV and 285eV and a second peak between 285eV and 286eV, respectively, the material of the electrolyte core comprises one or more of an oxide solid electrolyte, a halide solid electrolyte and a polymer solid electrolyte, the carbon coating layer also comprises an oxygen element, and the X-ray photoelectron spectrum test result of the carbon coating layer also has the following characteristics: the oxygen element has peaks between 530eV and 532eV and 528eV and 530eV; The positive electrode of the battery comprises a positive electrode active layer, and the carbon-coated solid electrolyte is disposed in the positive electrode active layer; or, The positive electrode of the battery comprises a positive electrode active layer and an ion-conducting layer which are stacked, and the carbon-coated solid electrolyte is arranged in the ion-conducting layer; or, The battery comprises a positive electrode, a negative electrode and a separator arranged between the positive electrode and the negative electrode, and the carbon-coated solid electrolyte is arranged on a side of the separator close to the positive electrode.

2. The battery according to claim 1, characterized in that The thickness of the carbon coating layer is 1 nm to 100 nm.

3. The battery according to claim 1, characterized in that The oxide solid electrolyte is selected from one or more of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium lanthanum zirconium oxide and lithium phosphorus oxygen nitrogen; The halide solid electrolyte is selected from one or more of lithium indium chloride, lithium yttrium chloride and lithium zirconium chloride.

4. The battery according to any one of claims 1 to 3, characterized in that: The particle size of the electrolyte core is 100nm~100μm.

5. The battery according to any one of claims 1 to 3, characterized in that: The positive electrode active layer includes a positive electrode active material, and the positive electrode active material is selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, layered ternary positive electrode material, spinel lithium nickel manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese phosphate and lithium cobalt phosphate.

6. The battery according to any one of claims 1 to 3, characterized in that: The negative electrode of the battery comprises a negative electrode plate, and the negative electrode plate comprises a negative electrode current collector and a negative electrode active layer arranged on the negative electrode current collector.

7. The battery according to any one of claims 1 to 3, characterized in that: The battery is a solid-state battery or a semi-solid-state battery.

8. An electrical device, characterized in that: The electrical device comprises a functional body and a battery as described in any one of claims 1 to 7, and the battery is used to supply energy to the functional body.

Citation Information

Patent Citations

  • Carbon-coated lithium aluminum titanium phosphate solid electrolyte as well as preparation method and application thereof

    CN116914237A

  • Coated particle for lithium ion secondary battery, positive electrode active material layer for lithium ion secondary battery, and lithium ion secondary battery

    JP2016072177A